Re-Examining "Solange I": Constitutionalism Beyond the State and the Role of Domestic Constitutional Courts - Andrej Lang; Kriszta Kovács; Mattias Kumm (Zeitschrift für ausländisches öffentliches Recht und Völkerrecht (ZaöRV) / Heidelberg Journal of International Law (HJIL), 2025)
Fifty years have passed since the Federal Constitutional Court (FCC) rendered one of its most widely discussed and influential decisions: Solange I. On May 29, 1974, the FCC famously held that it would review European Community law by the standards of German constitutional law for so long as the Community had not received a catalogue of fundamental rights, which is adequate in comparison with the catalogue contained in the German Basic Law.1 Only a handful of cases may qualify to potentially celebrate them in fifty years' time. Solange I is one of them. Why? What intellectual and institutional aspects of this decision are worth celebrating and preserving in Europe and beyond?
Keywords: 320